Object in German and Persian: A Short Study - Goodarzi, Aida Saidi Tavakoli (International Journal of Psychosocial Rehabilitation, 2020)
Object in German has different types and this misleads the students. Verbs in German have the feature of “capacity” and determine the type of object in the sentence. In present essay, we have sought to compare object in Persian and German and study their differences and similarities.